A Return to the Origin of the EMGS: Rejuvenating the Quest for Human Germ Cell Mutagens and Determining the Risk to Future Generations. (10th October 2019) - Marchetti, Francesco; Douglas, George R.; Yauk, Carole L.
Abstract : Fifty years ago, the Environmental Mutagen Society (now Environmental Mutagenesis and Genomics Society) was founded with a laser‐focus on germ cell mutagenesis and the protection of "our most vital assets"—the sperm and egg genomes. Yet, five decades on, despite the fact that many agents have been demonstrated to induce inherited changes in the offspring of exposed laboratory rodents, there is no consensus on whether human germ cell mutagens exist. We argue that it is time to reevaluate the available data and conclude that we already have evidence for the existence of environmental exposures that impact human germ cells. What is missing are definite data to demonstrate a significant increase in de novo mutations in the offspring of exposed parents. We believe that with over two decades of research advancing knowledge and technologies in genomics, we are at the cusp of generating data to conclusively show that environmental exposures cause heritable de novo changes in the human offspring. We call on the research community to harness our technologies, synergize our efforts, and return to our Founders' original focus. The next 50 years must involve collaborative work between clinicians, epidemiologists, genetic toxicologists, genomics experts and bioinformaticians to precisely define how environmental exposures impact germ cell genomes. It is time for the research and regulatory communities to prepare to interpret the coming outpouring of data and develop a framework for managing, communicating and mitigating the risk of exposure to human germ cell mutagens. Environ. Mol. Mutagen. 61:42–54, 2020. © 2019 Her Majesty the Queen in Right of Canada